112k views
0 votes
Simplify (5+1)^2-(12+3^2)/3

User Ihdina
by
5.3k points

2 Answers

6 votes

Good evening ,

Answer:

=29

___________________

Explanation:

Look at the photo below for the details.

Simplify (5+1)^2-(12+3^2)/3-example-1
User Smyrgl
by
5.5k points
6 votes

Answer:

29

Explanation:

Simplify the expression
(5+1)^2-(12+3^2)/(3) step by step:

1.


(5+1)^2=6^2=6\cdot 6=36

2.


(12+3^2)/(3)=(12+3\cdot 3)/(3)=(12+9)/(3)=(21)/(3)=7

Now,


(5+1)^2-(12+3^2)/(3)=36-7=29

User Aqif Hamid
by
5.8k points